Unusual chemical transformations of a germacrane ester from Ferulago antiochia Saya & Miski; A natural pro-drug in disguise? - Miski, Mahmut; Mabry, Tom J.; Davis, Patrick J. (Thieme Gruppe, 2012)
[Abstract Not Available]
International Congress on Natural Products Research on Global Change, Natural Products and Human Health/8th Joint Meeting of AFERP, ASP, GA, PSE and SIF -- JUL 28-AUG 01, 2012 -- New York, NY
WOS: 000307042801555
Keywords: Saya & Miski; Ferulago Antiochia; Germacrane Ester